Belgian Culex pipiens pipiens are competent vectors for West Nile virus while Culex modestus are competent vectors for Usutu virus. - Alina Soto; Lander De Coninck; Ann-Sophie Devlies; Celine Van De Wiele; Ana Lucia Rosales Rosas; Lanjiao Wang; Jelle Matthijnssens; Leen Delang (Public Library of Science (PLoS), 2023)
Background West Nile virus (WNV) and Usutu virus (USUV) are emerging arthropod-borne viruses (arboviruses) in Europe transmitted by Culex mosquitoes. In Belgium, it is currently unknown which Culex species are competent vectors for WNV or USUV and if these mosquitoes carry Wolbachia, an endosymbiotic bacterium that can block arbovirus transmission. The aims of our study were to measure the vector competence of Belgian Culex mosquitoes to WNV and USUV and determine if a naturally acquired Wolbachia infection can influence virus transmission. Methodology/principal findings Female Culex mosquitoes were captured from urban and peri-urban sites in Leuven, Belgium and offered an infectious bloodmeal containing WNV lineage 2, USUV European (EU) lineage 3, or USUV African (AF) lineage 3. Blood-fed females were incubated for 14 days at 25°C after which the body, head, and saliva were collected to measure infection, dissemination, and transmission rates as well as transmission efficiency. Mosquito species were identified by qRT-PCR or Sanger sequencing, the presence of infectious virus in mosquitoes was confirmed by plaque assays, and viral genome copies were quantified by qRT-PCR. Culex pipiens pipiens were able to transmit WNV (4.3% transmission efficiency, n = 2/47) but not USUV (EU lineage: n = 0/56; AF lineage: n = 0/37). In contrast, Culex modestus were able to transmit USUV (AF lineage: 20% transmission efficiency, n = 1/5) but not WNV (n = 0/6). We found that the presence or absence of Wolbachia was species-dependent and did not associate with virus transmission. Conclusions/significance This is the first report that Belgian Culex mosquitoes can transmit both WNV and USUV, forewarning the risk of human transmission. More research is needed to understand the potential influence of Wolbachia on arbovirus transmission in Culex modestus mosquitoes.